The Development of speed Transitional and Kinematic and their impact with some basic offensive and defensive skills in basketball for female students - MOHAMMED AMEEN, NADA (International Journal of Psychosocial Rehabilitation, 2020)
In recent years, great progress has been made in the field of education, and the educational process has received great interest from researchers and specialists, in order to keep pace with progress and reach the best education that students can access. One of the quick games that are taught in colleges within a curriculum that contains the basic offensive and defensive vocabulary of the game. Its performance requires a fast transition and mobility in line with the specificity of the game and its positions, and here lies the importance of research, and the problem of research lies in the movement of students while performing offensive and defensive skills as they are. Not at the required level and slow movement and performance, and the research aims to identify the differences between the pre and post tests to develop translation speed and movement of students, as well as to identify the differences in some offensive and defensive tests. The researcher used the experimental method in one experimental method with an experimental group, and it was conducted on a random sample of (4) four individuals and (20) ten students, at a rate of 19.42%. The subsequent preliminary tests for the research variables, and the search continued (21/10/2019 until 30/12/2019 AD), in addition to using appropriate statistical methods. The emergence of a big difference in the development of the navel and transitional movement, as well as in some offensive and defensive skills for students, and the researcher recommends practicing mobility, movement and diversification exercises within the practical lessons of their role. In influencing the performance of technically gifted students, offensive and defensive.